Packaging designs and recurring purchase intention of baby milk powder - Ng, Kim-Soon; Ahmad, Abd Rahman; Borhanudin, Nur Atikah (JARDCS, 2018)
Packaging retains the freshness and quality of food product. The visual and verbal characteristics of the package designs communicate the products message, nutritional facts, allergy warnings and other related information that convey the manufacturers commitment of products that are appealing to their consumers to positively influence purchase decisions. Previous studies found that the relationship between the characteristics of baby milk powder packaging with consumers purchasing intention is inconsistent and it needs further study. This study was thus conducted to investigate the relationship between the characteristics of visual and verbal packaging of infant milk powder with buyers or parents recurring purchase intention. The respondents are the buyers or parents who went to a hypermarket located in Batu Pahat town, Malaysia to buy baby milk powder for their baby aged between 0-6 years of age. Quantitative methodology using survey questionnaire has been used to collect the data through convenient purposive sampling. A total of 217 set of data collected were analyzed by regression analysis. It was found that the visual and verbal packaging characteristics are positively related with buyer recurring purchase intention of baby milk powder for their baby. It explains as much as 23.2% at p <0.001 in affecting buyer recurring purchase intention. Manufacturers should focus on the characteristics of the packaging both visually and verbally to attract their customers who buy baby milk powder